Representações sociais sobre família e abrigo: um estudo com crianças em situação de acolhimento institucional - Alexandre, Tátia Mirellis de Oliveira (2017)
ABSTRACT: The family is shown as a socio-historical institution, and it is considered the main social group responsible by the individual’s development. However, when there are situations of risk and social vulnerability, children and adolescents are temporarily removed from their families and transferred to institutional care centers. In this scenario, this work aimed to know and analyze the social representation of family and shelter to institutionalized children. The Social Representation Theory (Moscovici, 1978) was used as theoretical support and this theory allows the individual to build a referential on a significant one that is on his everyday reality, interfering on his behavior. Thirteen institutionalized children aged between seven to twelve years old participated in the study. The following instruments were used: sociodemographic questionnaire, semi-structured interview, and Drawing-Story Technique. The sociodemographic data were analyzed through descriptive statistics, and the semi-structured interview and the drawing-story went through content analysis of the Bardin, 1977. The results shows that family is perceived as a group of people affectively linked, and living in the same place, and have conditions to guarantee its members basics need; The shelter was represented mostly as a place that guarantees children's basics need and leisure actives. In addition, the participants linked the shelter as an environment with attachments similar to a family environment, highlighting the presence of the foster care and other children as elements that brings to the shelter the image of family. The institution does not fully fill the idea of family, which generates ambivalent feelings and negative affections towards the shelter. It was also observed that the participants perceive the prejudice of society and are often represented by pejorative terms that interfere negatively in the construction of the children's self-image and social identity. As a conclusion, the results may bases new reflections to performing of practical interventions in institutionalized children.